A comparative study of the rat populations and abundance of oriental rat fleas, plague vector in the Thailand-Malaysia border crossing areas, 2016-2018 - บุษบงค์, วิชุตา; เชี่ยวชาญยนต์, บงกช; รักแจ้ง, นิด; ไพบูลย์, สงฆ์ (Disease Control Journal, 2019)
Rat is a mammal that plays a major role in the transmission of infectious diseases and reservoirs host responsible for zoonotic diseases, which still remain a public health concern throughout the world, including Thailand. The objective of this survey was to examine the rat populations, other reservoir hosts and fleas abundance, represented as total ﬂea index. The survey was conducted at the Thailand-Malaysia land border crossing areas in eight points of entry located in the four southern border provinces. Research method was retrospective descriptive study using the animal reservoir survey form from 2015 to 2018. Data was analyzed using descriptive statistics. The results showed that rat trapping success rates in 2016, 2017, and 2018 were 17.91, 22.38, and 21.00 percent, respectively. The highest trap success rate was 44.00 percent, which was documented at Wang Prachan border crossing area in 2018. Three rat species (Rattas tanezumi, R. norvegicus and R. exulans) and one shrew species (Suncus murinus) were found at these sites. The highest number of captured rats were R. norvegicus (54.55%) at Padang Besar border crossing area in 2016, R. norvegicus (78.57%) at Sadao border crossing area in 2017, and both Sadao and Padang Besar border crossings registered the highest number of R. norvegicus (50.00%) in 2018. R. exulans (50.00%) was captured at Wang Prachan border crossing area more than the other sites in 2018. The total flea index was <1 in the eight different habitats. These data could be useful for the control of rodent and rat flea populations in each specific habitat.